Significant Ionospheric Hole and Equatorial Plasma Bubbles After the 2022 Tonga Volcano Eruption - Ercha Aa; Shun‐Rong Zhang; Philip J. Erickson; Juha Vierinen; Anthea J. Coster; Larisa P. Goncharenko; Andres Spicher; William Rideout (Space Weather)
Abstract This paper investigates the local and global ionospheric responses to the 2022 Tonga volcano eruption, using ground‐based Global Navigation Satellite System total electron content (TEC), Swarm in situ plasma density measurements, the Ionospheric Connection Explorer (ICON) Ion Velocity Meter (IVM) data, and ionosonde measurements. The main results are as follows: (a) A significant local ionospheric hole of more than 10 TECU depletion was observed near the epicenter ∼45 min after the eruption, comprising of several cascading TEC decreases and quasi‐periodic oscillations. Such a deep local plasma hole was also observed by space‐borne in situ measurements, with an estimated horizontal radius of 10–15° and persisted for more than 10 hr in ICON‐IVM ion density profiles until local sunrise. (b) Pronounced post‐volcanic evening equatorial plasma bubbles (EPBs) were continuously observed across the wide Asia‐Oceania area after the arrival of volcano‐induced waves; these caused a Ne decrease of 2–3 orders of magnitude at Swarm/ICON altitude between 450 and 575 km, covered wide longitudinal ranges of more than 140°, and lasted around 12 hr. (c) Various acoustic‐gravity wave modes due to volcano eruption were observed by accurate Beidou geostationary orbit (GEO) TEC, and the huge ionospheric hole was mainly caused by intense shock‐acoustic impulses. TEC rate of change index revealed globally propagating ionospheric disturbances at a prevailing Lamb‐wave mode of ∼315 m/s; the large‐scale EPBs could be seeded by acoustic‐gravity resonance and coupling to less‐damped Lamb waves, under a favorable condition of volcano‐induced enhancement of dusktime plasma upward E×B drift and postsunset rise of the equatorial ionospheric F‐layer.